EFEKTIVITAS PENAMBAHAN SUKROSA DAN SUSU SKIM TERHADAP KARAKTERISTIK YOGHURT NANAS (Ananas comosus) SEBAGAI PENGAYAAN MODUL KONSEP MIKROBIOLOGI PANGAN DALAM MATAKULIAH MIKROBIOLOGI DASAR - Novita Sri Wahyuni Sri Wahyuni; Irda Sayuti Irda Sayuti; Sri Wulandari Sri Wulandari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : This research aimed at studying the role of Lactic Acid Bacteria (LAB) in food stuffs on October-November 2014. Sucrose and skim milk is used as a source of energy and nutrients for LAB. The result of research was used to development a learning Module in basic microbiology course. This research was implemented in two steps, they are laboratory research and development a learning Module by use of ADDIE (Analyze, Design, Development, Implementation and Evaluation) development. Pineapple’s yoghurt manufacture begins with the stage of pasteurization, cooling, inoculation and incubation. This research results in the form of lactic acid levels, pH, protein content, carbohydrate content and moisture content are developed as a learning Module in the concept of food microbiology to enrich teaching materials in basic microbiology course.Keywords : Lactic Acid Bacteria, Sucrose, Skim milk, Learning Module